Effect of estrogen upon cyclic ADP ribose metabolism: β-Estradiol stimulates ADP ribosyl cyclase in rat uterus - Chini, Eduardo N. (The National Academy of Sciences of the USA, 1997)
Cyclic ADP ribose (cADPR) has been shown to trigger Ca(2+) release from intracellular stores through ryanodine receptor/channel. In our previous study we observed that all-trans-retinoic acid stimulates cADPR synthesis by ADP ribose cyclase (ADPR cyclase) in cultured epithelial cells. We have now investigated whether cADPR may play a signaling role in action of β-estradiol (E(2)), an archetypal steroid superfamily hormone, upon its major target organ, uterus, in vivo. Administration of E(2) to gonadectomized rats (0.2 mg/kg per day for 7 days) resulted in an ≈Δ + 300% increase of ADPR cyclase activity in extracts from uterus, but in liver, brain, or skeletal muscle ADPR cyclase was unchanged. Most of the E(2)-stimulated uterine ADPR cyclase was associated with membranes. The higher ADPR cyclase activity in response to E(2) was due to the increase of V(MAX) without change in K(m). Simultaneous administration of estrogen antagonist tamoxifen (8 mg/kg per day) with E(2) (0.2 mg/kg per day) prevented an increase in ADPR cyclase. In uterine extracts from E(2)-treated rats, the rate of cADPR inactivation by cADPR hydrolase and the activity of NADase was increased, but to a much lesser degree than activity of ADPR cyclase. Our results indicate that E(2), via action to its nuclear receptors in vivo, increases ADPR cyclase activity in uterus. We propose that some of the estrogen effects, and by extension the effects of other steroid superfamily hormones, upon specialized cellular functions and upon hormone-induced gene expression in target cells, are mediated by cADPR-Ca(2+) release pathway.